Assessment of acute head injury in an emergency department population using sport concussion assessment tool – 3rd edition. Issue 2 (4th March 2018) - Bin Zahid, Abdullah; Hubbard, Molly E.; Dammavalam, Vikalpa M.; Balser, David Y.; Pierre, Gritz; Kim, Amie; Kolecki, Radek; Mehmood, Talha; Wall, Stephen P.; Frangos, Spiros G.; Huang, Paul P.; Tupper, David E.; et al.
ABSTRACT: Sport Concussion Assessment Tool version 3 (SCAT-3) is one of the most widely researched concussion assessment tools in athletes. Here normative data for SCAT3 in nonathletes are presented. The SCAT3 was administered to 98 nonathlete healthy controls, as well as 118 participants with head-injury and 46 participants with other body trauma (OI) presenting to the ED. Reference values were derived and classifier functions were built to assess the accuracy of SCAT3. The control population had a mean of 2.30 ( SD = 3.62) symptoms, 4.38 ( SD = 8.73) symptom severity score (SSS), and 26.02 ( SD = 2.52) standardized assessment of concussion score (SAC). Participants were more likely to be diagnosed with a concussion (from among healthy controls) if the SSS > 7; or SSS ≤ 7 and SAC ≤22 (sensitivity = 96%, specificity = 77%). Identification of head injury patients from among both, healthy controls and body trauma was possible using rule SSS > 7 and headache or pressure in head present, or SSS ≤ 7 and SAC ≤ 22 (sensitivity = 87%, specificity = 80%). In this current study, the SCAT-3 provided high sensitivity to discriminate acute symptoms of TBI in the ED setting. Individuals with a SSS > 7 and headache or pressure in head, or SSS ≤ 7 but with a SAC ≤ 22 within 48-hours of an injury should undergo further testing.